Teachers' transformative learning on digital afterlife. Issue 2 (3rd April 2023) - Ben-Atar, Ella; Ben-Asher, Smadar
Abstract: Death and its repercussions do not usually associate with youth education. However, the issue of digital inheritance may be used to demonstrate how teachers can promote their students and their own critical thinking about digital media. The current study examined a course in which 104 teachers learned about digital inheritance. The research question concerned the teachers' reaction to the emotionally charged subject matter. Data were analyzed using Mezirow's (2003) model of Transformative Learning and included teachers' feedback on the course. The findings point to the advantage of focused exposure to new and sensitive content within a defined framework of teachers' professional development, as such a framework allows the learners to express resistance to the emotionally difficult topic. A conclusion from the research is that relevant but unfamiliar life content related to media literacy should be integrated into teachers' professional development.